Oral Senescence: From Molecular Biology to Clinical Research - Parkinson, Eric Kenneth; Prime, Stephen Stewart (Frontiers in Dental Medicine, 2022)
Cellular senescence is an irreversible cell cycle arrest occurring following multiple rounds of cell division (replicative senescence) or in response to cellular stresses such as ionizing radiation, signaling imbalances and oxidative damage (stress-induced premature senescence). Even very small numbers of senescent cells can be deleterious and there is evidence that senescent cells are instrumental in a number of oral pathologies including cancer, oral sub mucous fibrosis and the side effects of cancer therapy. In addition, senescent cells are present and possibly important in periodontal disease and other chronic inflammatory conditions of the oral cavity. However, senescence is a double-edged sword because although it operates as a suppressor of malignancy in pre-malignant epithelia, senescent cells in the neoplastic environment promote tumor growth and progression. Many of the effects of senescent cells are dependent on the secretion of an array of diverse therapeutically targetable proteins known as the senescence-associated secretory phenotype. However, as senescence may have beneficial roles in wound repair, preventing fibrosis and stem cell activation the clinical exploitation of senescent cells is not straightforward. Here, we discuss biological mechanisms of senescence and we review the current approaches to target senescent cells therapeutically, including senostatics and senolytics which are entering clinical trials.